2018
DOI: 10.1111/1753-0407.12853
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preoperative hepatitis B virus infection, hepatitis C virus infection, and coinfection on the development of new‐onset diabetes after kidney transplantation

Abstract: Preoperative HCV infection significantly increased the risk of NODAT in Chinese KTRs, whereas HBV infection and HBC + HCV coinfection were not correlated with NODAT development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
(99 reference statements)
2
2
0
Order By: Relevance
“…52 In the present study, we observed that there was a significantly higher prevalence of patients with chronic HCV infection in the PTDM group, especially among cases with the AT genotype (Tables 1 and 4). This finding was in accordance with previous studies that highlighted chronic HCV as a risk factor for PTDM. 53 There was a significantly higher prevalence of AA and AT genotypes in the PTDM group ( p =0.05 and 0.007, respectively), especially in those with HCV infection (Table 4).…”
Section: Discussionsupporting
confidence: 92%
“…52 In the present study, we observed that there was a significantly higher prevalence of patients with chronic HCV infection in the PTDM group, especially among cases with the AT genotype (Tables 1 and 4). This finding was in accordance with previous studies that highlighted chronic HCV as a risk factor for PTDM. 53 There was a significantly higher prevalence of AA and AT genotypes in the PTDM group ( p =0.05 and 0.007, respectively), especially in those with HCV infection (Table 4).…”
Section: Discussionsupporting
confidence: 92%
“…As for pre-transplant diabetes, the prevalence of AGM (10.7%) or NODAT (12.6%) among our KT recipients was lower than that reported in the literature (> 20%) [12,13,37]. Such reassuring results may be partially due to the favorable baseline characteristics of the patients enrolled [38], mostly Caucasian [39,40], young [9,40], non-obese (mean BMI, 23) [40], and without a history of chronic HBV (3.3%) or HCV (6.7%) [41] infection. However, other variables may have played a role, such as the preferred use of cyclosporine over tacrolimus in recipients at increased risk of NODAT [42,43], routine application of CNIminimization protocols [44], paucity of patients receiving mTORi (<3%) [45], relatively low doses of steroid administered at induction (≤750 mg) [46], frequent (twice weekly) CMV viremia assessment during the early post-transplant phase [17], dedicated counselling for optimal weight control after transplant [47], and aggressive outpatient monitoring for hypertension [48], lipid disorders [44], magnesium [16], or vitamin D deficiency [9].…”
Section: Discussionsupporting
confidence: 43%
“…In particular, familial predisposition to diabetes [9], older age [50], and higher BMI [51] have been consistently reported as important contributing factors. On the contrary, less clear remain the possible relationships between NODAT and autosomal polycystic kidney disease [52], HCV [53], or HBV infection [41].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-transplant chronic HCV infection (p = 0.023) and cyclosporine use (p = 0.024) were the most significant predictors of PTDM. In a retrospective cohort of 557 renal transplant recipients from China, HCV infection was associated with a 3.03-fold risk of PTDM on multivariate analysis [ 15 ]. In a meta-analysis involving 2,502 renal transplant recipients from 10 studies, a strong association was found between pre-transplant anti-HCV antibody positivity and PTDM with an adjusted HR of 3.97 [ 16 ].…”
Section: Discussionmentioning
confidence: 99%